2010
DOI: 10.1074/jbc.m109.045948
|View full text |Cite
|
Sign up to set email alerts
|

Human GTSE-1 Regulates p21CIP1/WAF1 Stability Conferring Resistance to Paclitaxel Treatment

Abstract: p21CIP1/WAF1 belongs to the CIP/KIP family of Cdk inhibitors, and its expression is tightly controlled during the cell cycle, mainly by transcriptional and post-translational mechanisms. Fine regulation of p21 CIP1/WAF1 levels is critical for cell cycle control and for cellular response to stress. In the present work, we describe a novel mechanism to modulate p21 CIP1/WAF1 levels mediated by the human GTSE-1 (G 2 and S phase-expressed-1) protein. Our results provide evidence that hGTSE-1 protects p21 CIP1/WAF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…In addition to radiation resistance, FKBPL plays a significant role in tumor progression (Robson et al 1997;Robson et al 1999;Robson et al 2000;Jascur et al 2005). In tumor cells, FKBPL appears to participate in not only growth of the tumor, but also in the sensitivity of the tumor to various chemotherapeutic agents (Bublik et al 2010). For example, high levels of GSTE-1 interact with the FKBPL/ Hsp90/p21 complex, which leads to p21 stabilization leading to resistance to the chemotherapeutic agent Taxane (Bublik et al 2010).…”
Section: Fkbplmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to radiation resistance, FKBPL plays a significant role in tumor progression (Robson et al 1997;Robson et al 1999;Robson et al 2000;Jascur et al 2005). In tumor cells, FKBPL appears to participate in not only growth of the tumor, but also in the sensitivity of the tumor to various chemotherapeutic agents (Bublik et al 2010). For example, high levels of GSTE-1 interact with the FKBPL/ Hsp90/p21 complex, which leads to p21 stabilization leading to resistance to the chemotherapeutic agent Taxane (Bublik et al 2010).…”
Section: Fkbplmentioning
confidence: 98%
“…In tumor cells, FKBPL appears to participate in not only growth of the tumor, but also in the sensitivity of the tumor to various chemotherapeutic agents (Bublik et al 2010). For example, high levels of GSTE-1 interact with the FKBPL/ Hsp90/p21 complex, which leads to p21 stabilization leading to resistance to the chemotherapeutic agent Taxane (Bublik et al 2010). Although the exact radio-and chemo-protective role of FKBPL needs to be elucidated, the data clearly show that FKBPL is an important factor in cell-cycle progression, cell survival, and tumor progression.…”
Section: Fkbplmentioning
confidence: 99%
“…, and a reduction in the DNA repair 191,192 . All of these FKBPL-related roles are associated with intracellular FKBPL however more recently, an extracellular role for FKBPL was identified.…”
Section: The Role Of Ppiases In Cancermentioning
confidence: 99%
“…A number of publications have demonstrated that this transport mechanism first proposed for the GR is used by several other factors such as the AAV-2 (adeno-associated virus-2) [66], poly-glutamine aggregated proteins in Kennedy disease cells [67], the brain specific protein PAHX-AP1 [68], the proapoptotic factor p53 [65], the cell cycle arresting protein p21 [69], the mineralocorticoid receptor (MR) [36], FKBPL/DIR1/WisP39 client proteins [62], the transcription factor RAC3 [70], the ecdysone receptor [71], and so on. Moreover, the interaction between dynein and IMMs has also been found in plants [72], suggesting that the functional role of this complex has been preserved during the evolution.…”
Section: The Hsp90•fkbp52•dynein/dynactin Molecular Machinery Of Tranmentioning
confidence: 99%
“…In addition to radiation resistance, FKBPL/WisP39 plays a significant role in tumor progression [150,152,155,157]. In tumor cells, FKBPL/WisP39 favors the tumor growth and it is also related to the sensitivity of the tumor to chemotherapeutic compounds [158].…”
Section: Tpr-domain Immunophilins In Cancermentioning
confidence: 99%